Systematic review of partial hepatic resection to treat hepatic metastases in patients with gastric cancer. Issue 44 (November 2016) - Long, Di; Yu, Peng-Cheng; Huang, Wei; Luo, Yu-Long; Zhang, Sen
Abstract: Objective: To examine overall survival and mortality following hepatic resection in patients with hepatic metastases from gastric cancer. Methods: EMBASE, PubMed, Web of Science, and Cochrane databases were systematically searched for publications involving more than 10 patients who underwent hepatic resection to treat hepatic metastases from gastric cancer and who did not have peritoneal disease or involvement of other distant organs. Results: A total of 39 studies were included, involving a median of 21 hepatic resections (range, 10–64). Resection was associated with median 30-day morbidity of 24% (range, 0%–47%) and 30-day mortality of 0% (range, 0%–30%). Median overall survival was 68% at 1 year, 31% at 3 years, and 27% at 5 years. Asian studies reported higher rates than Western studies for overall survival at 1 year (73% vs 59%), 3 years (34% vs 25%), and 5 years (27% vs 17%). Compared with palliative treatment, resection was associated with significantly lower mortality at 1 year (risk ratio [RR] 0.47, P  < 0.001) and 2 years (RR 0.70, P  < 0.001). Conclusion: Patients with hepatic metastases from gastric cancer may benefit from hepatic resection in case of good physical condition, absence of peritoneal dialysis, and optimum liver function with single metastases. More trials are needed to confirm this finding.